OPERATIONAL RISK MANAGEMENT AT PT WARUNG PINTAR SEKALI - LARASATI SALSABILA SARWONO, NADA
PT Warung Pintar Sekali that known as Warung Pintar is a partnership-based retail-technology startup that focuses on developing micro-medium businesses with the uses of technologies such as Internet of Things (IoT), big data analytics, dan blockchain. Each person who partnered with Warung Pintar will be lent a cart and its supporting electronic equipment, supported by with centralized goods procurement system, and guided in conducting daily business. During its journey, Warung Pintar experienced several cases which resultes in substantial financial losses. These cases encourage Warung Pintar to develop risk management plan so that in the future, they can take preventive and mitigation steps to minimize the impact of a failure in the company’s business processes. The standard used to design risk management is ISO 31000:2018. The risk management process is divided into four stages; business process mapping, risk identification, risk analysis, and risk evaluation. Business process mapping was done by using an adaptation of the Process Classification Framework issued by the American Productivity and Quality Center (APQC). The method used for risk identification and risk measurement is Failure Mode and Effect Analysis (FMEA), a method that measures three aspects in a risk; severity, occurrence, and detection. Then, a risk evaluation based on the company's risk criteria was carried out to determine the list of critical risks. Each critical risk then analysed with Bow-Tie Analysis to determine its preventive and mitigation steps based on the results of risk, cause, and effect relationship mapping. Impact/Effort Matrix or the Action Priority Matrix was used to determine implementation priorities of each proposed risk response. The number of risks identified through Warung Pintar's core business process mapping is 135 risks with 185 combinations of potential impacts, potential causes, and current process controls. Based on the results of risk measurement and determination of critical risk using company risk criteria, there are 57 risks that are classified as critical. The total number of risk response proposals for all critical risks is 88 proposals. The Impact/Effort Matrix of risk response proposals resulted in 42 proposals classified as quick wins, 28 proposals as major projects, and 18 proposals as fill ins.